If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.9(8 + -1x) = 1.7(6 + -1x) (8 * 1.9 + -1x * 1.9) = 1.7(6 + -1x) (15.2 + -1.9x) = 1.7(6 + -1x) 15.2 + -1.9x = (6 * 1.7 + -1x * 1.7) 15.2 + -1.9x = (10.2 + -1.7x) Solving 15.2 + -1.9x = 10.2 + -1.7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.7x' to each side of the equation. 15.2 + -1.9x + 1.7x = 10.2 + -1.7x + 1.7x Combine like terms: -1.9x + 1.7x = -0.2x 15.2 + -0.2x = 10.2 + -1.7x + 1.7x Combine like terms: -1.7x + 1.7x = 0.0 15.2 + -0.2x = 10.2 + 0.0 15.2 + -0.2x = 10.2 Add '-15.2' to each side of the equation. 15.2 + -15.2 + -0.2x = 10.2 + -15.2 Combine like terms: 15.2 + -15.2 = 0.0 0.0 + -0.2x = 10.2 + -15.2 -0.2x = 10.2 + -15.2 Combine like terms: 10.2 + -15.2 = -5 -0.2x = -5 Divide each side by '-0.2'. x = 25 Simplifying x = 25
| 6(k-3)= | | 3+x=x-2 | | 3+c=2-2c | | 0.9x-19=1.6x-26 | | x^2+20x-400=0 | | x+2x+(2x+8)=73 | | R^2=35+2r | | d-7=-4 | | -(3y+1)-(-2y-5)=1 | | X^2=-4-5x | | 2(7+x)-6=10 | | 3(9-3x)=9 | | 5x-45y=-30 | | 2y+13=5y+7 | | ((1-x)/2)-((x-2)/3)=-x/4 | | -4-2z=6 | | (2.5x)-(x)+4000=b | | 2x^2+20x-400=0 | | -0.3x^2+1.75x+1.25=0 | | 5+5+x=17 | | 24a/(x-24)=12a/30 | | x+y=(-4) | | -56=-2(5w+8)-(3w-12) | | 6(4x-2)=3(8x+8) | | 4m+2.3=9.2 | | -(7x-3)= | | 7(2x+3)-6=43 | | 9-2x=-7x+49 | | 8-(6x-4)=-48 | | 9+x^2=49 | | 7+2s-1=9s+24-5s | | 4(x+1)+5(x+6)= |